2019
DOI: 10.3389/fpsyg.2019.00482
|View full text |Cite
|
Sign up to set email alerts
|

Trusting Robocop: Gender-Based Effects on Trust of an Autonomous Robot

Abstract: Little is known regarding public opinion of autonomous robots. Trust of these robots is a pertinent topic as this construct relates to one’s willingness to be vulnerable to such systems. The current research examined gender-based effects of trust in the context of an autonomous security robot. Participants (N = 200; 63% male) viewed a video depicting an autonomous guard robot interacting with humans using Amazon’s Mechanical Turk. The robot was equipped with a non-lethal device to deter non-authorized visitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 38 publications
0
26
2
Order By: Relevance
“…Finally, the sample size in the conditions of the TC phase, in which feedback and reliability influences on human trust were investigated, is relatively small to draw generalizable conclusions. This might also be the reason why we were not able to find any statistically significant differences between men and women in trust which does not conform with previous studies where women reported higher trust in Gallimore et al (2019) and lower trust in Schuster et al (2015) than men. A larger sample size would better represent the population allowing for the use of parametric tests and enhancing the power and generalizability of the results.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Finally, the sample size in the conditions of the TC phase, in which feedback and reliability influences on human trust were investigated, is relatively small to draw generalizable conclusions. This might also be the reason why we were not able to find any statistically significant differences between men and women in trust which does not conform with previous studies where women reported higher trust in Gallimore et al (2019) and lower trust in Schuster et al (2015) than men. A larger sample size would better represent the population allowing for the use of parametric tests and enhancing the power and generalizability of the results.…”
Section: Discussioncontrasting
confidence: 97%
“…We will refer to the first group as G1 and the second one as G2 . Different research work suggests that there is a difference between men and women in terms of trust [e.g., trust games in economics ( Dittrich, 2015 ), human robot interaction ( Gallimore et al, 2019 ), and human automation interaction ( Schuster et al, 2015 )]. Therefore, we made sure that the number of men and women was equal in the groups.…”
Section: Methodsmentioning
confidence: 99%
“…PTR is discussed as the extent to which the consumers sense that the chatbot/robot is reliable and credible (Yagoda and Gillan, 2012; You et al , 2018; Gallimore et al , 2019). Consumers feel safe when trust is developed toward robots (You et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Along with TAM, context-specific variables concerning HRI (Bartneck et al , 2009; Deshmukh et al , 2018; Ho and Macdorman, 2010; Yu, 2020; Sheehan, 2018; Bartneck et al , 2007; Gray and Wegner, 2012) are considered to provide better explanatory power. The considered variables of HRI are ANM (Ruijten et al , 2019), PNT (Weiss and Bartneck, 2015; Petisca et al , 2015; McGinn et al , 2019; Hughes et al , 2015), PTR (Yagoda and Gillan, 2012; You et al , 2018; Gallimore et al , 2019) and technology anxiety (Evanschitzky et al , 2015; Mani and Chouk, 2018; Meuter et al , 2005). This study also explores the AUE of chatbots in tourism by investigating the association of AIN and AUE (Gupta et al , 2017; Ghanem et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, we are interested in exploring the role of user personality in perception of robot employment fit, as personality has been shown to be an individual difference that is predictive of responses to automation (Szalma & Taylor, 2011). Further, there has been very little research on individual differences in HRI, and what does exist examines constructs like robotic control (Chen & Barnes, 2012), and trust (Gallimore, Lyons, Vo, Mahoney, & Wynne, 2019;Oleson, Billings, Kocsis, Chen, & Hancock, 2011). Thus, we have included a measure of personality in our study of the influence of robot human-likeness on perceptions of robot fit across a range of job types to explore the how personality influences these perceptions.…”
Section: Introductionmentioning
confidence: 99%